The Synergy of Strategy and Engagement: Unlocking Social Media's Performance Potential - Roosdhani, Mohamad Rifqy; Arifin, Samsul; Ali, Ali; Komariyatin, Nurul; Huda, Nurul (Universitas Ciputra Surabaya, 2024)
This study aimed to examine the effectiveness of social media marketing strategies in improving the social media performance of Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage sector. This study uses a comprehensive analytical approach, including descriptive and inferential analysis, to evaluate data collected through questionnaires. The method used in this study is a quantitative approach with data collection from 265 SMEs in the food and beverage sector in the cities of Solo, Semarang, Kudus, and Jepara, which were selected using a purposive sampling method. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS software. This study results that the development of social media-based brand exposure and customer engagement is critical in driving improved social media performance. The study also provides detailed insights into respondents' perceptions of the research variables, including social media marketing strategy, social media-based customer engagement, brand exposure, and social media performance.